Clinical considerations for open versus endoscopic approaches in skull base surgery. Issue 4 (August 2022) - Jawad, Basit; Vankoevering, Kyle; Carrau, Ricardo; Patil, Yash
Abstract : Purpose of review: We aim to distill the current body of evidence to consider when selecting an endoscopic versus open approach to address cranial base disease. We evaluate the evolution of modern surgical techniques and their respective limitations. Recent findings: Greater understanding of the role of tumor biology in relation to patient outcomes has led to increasingly sophisticated treatment algorithms. This combined with further development of advanced instrumentation and technique has led to the adoption of new surgical corridors previously unapproachable via traditional surgery. Summary: Endoscopic and open craniofacial approaches both remain important surgical techniques in the management of cranial base tumors. The modern skull base surgeon may employ a combination of approaches to optimize tumor extirpation while preserving functional outcomes. Patient history, anatomic tumor extent, histology, and functional goals should be considered thoroughly when planning any surgical intervention.